Pengaruh Partisipasi Anggaran, Motivasi, dan Evaluasi terhadap Kinerja Manajerial pada Pemerintahan Kabupaten Situbondo - Sindy Afifa; Imam Mas'ud (Universitas Jember, 2018)
This study aims to examine the effect of budgetary participation, motivation, and evaluation of performance on managerial performance. The sample used in this study were 82 respondents consisting of the Head of department , head of section , head of the field , sub- section chief , and head of section of the Government Situbondo . The method used in this study is the purposive sampling method. This study uses primary data collected directly through questionnaires. In this study, the quality of test data used are validity and reliability testing. This study also uses the classical assumption that the test data normality, multicollinearity test, and test heteroskedastisitas. The analytical tool used is multiple linear regression analysis and t test. The results of this study indicate that budgetary participation and significant positive effect on managerial performance, motivation positive and significant impact on the performance, and evaluation of managerial performance and a significant positive effect on managerial performance. Keywords: participation of budgetary, motivation, evaluation, managerial performance